Astragalus Polysaccharide Attenuates Cisplatin-Induced Acute Kidney Injury by Suppressing Oxidative Damage and Mitochondrial Dysfunction. (8th January 2020) - Ma, Qing; Xu, Yao; Tang, Lumin; Yang, Xiaoqian; Chen, Zhejun; Wei, Yuehan; Shao, Xinghua; Shao, Xiaoguang; Xin, Zhixiang; Cai, Biao; Wang, Qi; Mou, Shan
Abstract : Cisplatin is a widely used chemotherapeutic drug in the treatment of various solid tumors. However, the cisplatin-induced acute kidney injury remains a disturbing complication, which still lacks effective prevention. Cisplatin-induced oxidative damage and mitochondrial dysfunction are anticipated to be crucial in the occurrence of kidney injury. Astragalus polysaccharide (APS) has been reported to possess multiple biological activities including anti-inflammatory, antioxidant, and mitochondria protection. In this study, we investigated the potentially protective effect of APS against cisplatin-induced kidney injury both in vivo and in vitro. We found that APS pretreatment attenuated the cisplatin-induced renal dysfunction and histopathological damage in mice; in addition, it also protected the viability of HK-2 cells upon cisplatin exposure. APS attenuated the cisplatin-induced oxidative damage by reducing reactive oxygen species (ROS) generation and recovering the activities of total superoxide dismutase and glutathione peroxidase in mice kidney. In addition, electron microscope analysis indicated that cisplatin induced extensive mitochondrial vacuolization in mice kidney. However, APS administration reversed these mitochondrial morphology changes. In HK-2 cells, APS reduced the cisplatin-induced mitochondrial and intracellular ROS generation. Furthermore, APS protected the normal morphology of mitochondria, blocked the cisplatin-induced mitochondrial permeability transition pore opening, and reduced the cytochrome c leakage. Subsequently, APS reduced the cisplatin-induced apoptosis in mice renal and HK-2 cells. In conclusion, our data suggested that APS pretreatment might prevent cisplatin-induced kidney injury through attenuating oxidative damage, protecting mitochondria, and ameliorating mitochondrial-mediated apoptosis.